Factors that are Related to The Condition of Passenger Ship Sanitation in Tanjung Perak Port Surabaya: Factors that are Related to The Condition of Passenger Ship Sanitation in Tanjung Perak Port Surabaya - setiawan, darma; Mindiharto, S.PSi., M.Kes, sestiono (Universitas Muhammadiyah Gresik, 2020)
Sanitation is an effort to prevent disease and environmental risk factors that become a chain of disease transmission. Ship sanitation applies to all types of ships both passenger ships and goods from within and outside the country. The purpose of the study was to analyze the factors related to the sanitary conditions of passenger ships at the Port of Tanjung Perak Surabaya, in 2019. The type of this research is correlational analytic with cross sectional design. The population is all passenger ships that dock at the port of Tanjung Perak Surabaya, with a total sample of 49 samples. The sampling method is by questionnaire and direct interview with respondents. Statistical tests using the Chi-Square Test. The results showed the average passenger ship leaning at the Port of Tanjung Perak Surabaya had a low risk sanitation level of 83.67% and a high level of risk of 16.33%. The relationship between the skipper's leadership style (pvalue = 0,0001), knowledge (pvalue 0.047), leaning time (pvalue = 0,0001), maintenance funds (pvalue = 0,0001), facilities and infrastructure (pvalue = 0,0001) with the level of health risks of the ship. From the results of the study it can be concluded that there is a relationship between the sanitary conditions of the ship and the leadership style of the skipper, the level of knowledge of the crew, the time of the ship berth, maintenance funds, facilities and infrastructure. The conclusion is that there is a relationship between the sanitary conditions of the ship and the leadership style of the skipper, the level of knowledge of the crew, the time the ship rests, maintenance funds, facilities and infrastructure. Passenger ships are expected to have good Standard Operating Procedures and are applied in maintaining vessel cleanliness.